Karakteristik Biopelet dari Serbuk Kayu dan Sekam Padi - Istaniah,; Ma'ruf, Amar; Rachmat, Ridwan; Wikan Widodo, Teguh (JURNAL AGROINDUSTRI HALAL, 2024)
As the main source of energy for the country, fossil fuels are used to fulfill the needs in every human activity such as cooking. People usually use kerosene and LPG, which are fossil fuels. The increasing use of fossil fuels is inversely proportional to the earth's reserves in nature. Currently, there is a scarcity of fossil fuels such as LPG and kerosene in several places. As petroleum reserves decrease, both LPG and kerosene also decrease. The use of biomass alternative energy sources is one way to solve the current energy problem. The abundant availability of waste from agricultural products is utilized as biomass renewable energy. This is also one of the alternatives to handling agricultural waste by becoming a renewable fuel, environmentally friendly and more economically valuable. This research aims to utilize rice husk into alternative fuel, analyze the characteristics and quality of a mixture of rice husk and sawdust. Biopelets in this study are made from rice husk and sawdust, there are 3 formulations, namely KS-1 husk content lower than KS-2, KS-2 husk content lower than KS-3. The best biopelet from the test results is biopelet with KS-3 formulation with a moisture content of 7.27%, density of 1.322 g/cm3, and calorific value of 3983.39 cal/g.